Incremental lines in root cementum of human teeth: An approach to their role in age estimation using polarizing microscopy - Aggarwal Pooja; Saxena Susmita; Bansal Puja (Wolters Kluwer Medknow Publications, 2008)
Age estimation is an important factor in the identification of an individual in forensic science. The hard tissues of the human dentition are able to resist decay and degradation long after other tissues are lost. This resistance has made teeth useful indicators for age calculation. Recent research indicates that tooth cementum annulations (TCA) may be used more reliably than any other morphological or histological traits of the adult skeleton for age estimation. The purpose of this study was to examine the correlation between age and the number of incremental lines in human dental cementum and to ascertain the best method of studying cementum with respect to different forms of microscopy. Thirty nonrestorable teeth were extracted from 20 people, and longitudinal ground section of each tooth was prepared. Photomicrographs of the area at the junction of apical and middle third of the root under light and polarized microscope were taken. The cementum was composed of multiple light and dark bands that were counted on the photomicrograph with the help of image analysis software and added to the average eruption time of individual tooth. The predicted age of the individual was thus obtained. Results showed a significant correlation between the predicted age and actual chronological age of the individual. These data indicate that quantitation of cementum annuli is a moderately reliable means for age estimation in humans and polarizing microscopy is a better means of visualizing incremental lines of cementum compared to light microscopy.